Молекулярно-генетичні методи в діагностиці гострих лейкемій - Дибков, М.В.; Завелевич, М.П.; Глузман, Д.Ф.; Поліщук, Л.О.; Малюта, С.С.; Телегеєв, Г.Д. (Фактори експериментальної еволюції організмів, 2013)
Aims. Acute leukemia - heterogeneous group of diseases characterized by the rapid growth of abnormal uncontrolled proliferation of hematopoietic stem cells or progenitor cells. The definition of specific cytogenetic-molecular abnormalities is important both for diagnosis and for treatment. Methods. Fusion genes bcr-abl1, mll/af4 and mll/af9 was detected by nested RT-PCR. Results. Samples of blood of patients with different type acute leukemia were analyzed. A case of simultaneous detection fusion genes p210 bcr-abl1, p190 bcr-abl1 and mll/af4 was detected. Conclusions. The proposed method for detection of the fusion genes mll/af4 and mll/af9 allows for molecular genetic differential diagnosis of acute leukemia.

Key words: acute leukemia, PCR, fusion genes mll/af4 mll/af9, diagnostics.